Penggunaan Media Sosial Sebagai Media Belajar Bahasa Inggris; Persepsi Mahasiswa - Hidya Maulida; Norliani (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
Social media can be utilized for language skills. Yunus, Salehi, & Chenzi (2012) stated that social media such as facebook and blogs will provide written language input to them so that they will develop their writing skills. This also facilitates students to learn new words and vocabulary that are suitable for them in writing (Khan, Ayaz, & Faheem, 2016). Social media can also improve students' speaking skills through conversations with native English speakers (Ehsan & Nasri, 2019).The study of learners' perceptions, in this case students, towards the use of social media for learning English is important to investigate because teachers, in this case lecturers, need to know their students' preferences in terms of what social media applications they use and how they use social media to learn English.The aim of this research is to describe the perceptions of students in the English Language Education Study Program regarding the use of social media for learning English; which social media platforms are commonly used to learn English and how they use them. This research uses a qualitative approach using questionnaires and interviews as data collection methods. Basic statistical analysis is used to analyse data from the questionnaires, and data from the interviews are analysed using the Miles and Huberman flow model. The results show that students in this study use 7 social media platforms to improve their English, and 3 of them are the most frequently used social media applications considered more suitable for their English learning needs. They chose YouTube as the most widely used social media for learning English. Furthermore, they stated that social media provides sources of English content to practice their English skills, expand their vocabulary knowledge, and improve their pronunciation. They also expressed challenges in using social media for learning, such as issues with internet connectivity, privacy, and inappropriate content.